The key role of sample analysis in Fukushima Dai-Ichi decommissioning, debris management, and accident progression investigation - Zubekhina, Bella; Pshenichnikov, Anton; Nagae, Yuji; Kurata, Masaki (Frontiers in Nuclear Engineering, 2023)
This review is an up-to-date report of the analysis of U-bearing samples from the Fukushima Daiichi Nuclear Power Station (1F). It summarizes the experience gained after previous severe nuclear accidents in the field of fuel debris analysis and the utilization of the results. Current methods of 1F sample analysis and the main results are presented with a discussion on future strategies of fuel debris analysis and the requirements for 1F decommissioning.